Land certification and farmers’ decision on long term investment in Jimma Zone, Southwest Ethiopia - Ermias Melaku Addis; Mequanent Muche Amera; Gedam Birhane Biru (Journal of Degraded and Mining Lands Management, 2020)
The impacts of land tenure security on investment have long been recognized. Land certification has been undertaking in most zones of the region including Jimma zone. Therefore this study assesses farmers’ perception on land certification and factors affecting long term land related investments specifically tree, fruit tree and coffee planting. It was conducted in three Woredas of Jimma Zone namely Omonada, Limmu Kossa and Seka Chekorsa. Multi-stage sampling techniques were employed to select respondent farmers from each Woreda and a total of 200 household heads, of which 79.5% are them secure land certification, were selected for the analysis. The findings’ indicates that most of the respondents have positive and strong agreements with different attributes of land certification. These are land certification encourage investment activities, soil conservation measures, and farmers to venture in area that could enhance productivity, provide increased land tenure, feel sense of ownership and current system is satisfactory, have lifelong use right and support both woman and man to share equally. There is significant relationship between land certification and long term land related investments specially tree and fruit planting. In addition long term land related investments are influenced by total land holding, land certification, oxen ownership, extension service and annual income. Thus, land certification and other socio-economics and institutional factors need to be considered to encourage farmers’ involvement in long term land related investments